Guidelines and Recommendations for Academic Bodies within the Framework of the Erasmus+ Project ECOLHE - Torchia, Luca (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
ECOLHE (E-learning in the European Higher Education Area) is a project co-financed by the Erasmus+ Programme of the European Union (project n. 2020-1-IT02-KA203-079176) in the field of KA203 - Strategic Partnerships for higher education. It started on 1st September 2020 and ended on 31 August 20232. The project involved partners from different countries: the Digital Technologies Education & Society (DiTES) research centre, Link Campus University, the Link Campus Foundation, the University of Roma Tre (Italy), the University of Patras (Greece), the University of Applied Sciences “Bachelor” (Finland), the University of Cork (Ireland), the University Oberta de Catalunya (Spain) and the EAEC (European Association for Erasmus Coordinators) network.